2011
DOI: 10.1007/s10608-011-9425-4
|View full text |Cite
|
Sign up to set email alerts
|

Habitual Sleep, Reasoning, and Processing Speed in Older Adults with Sleep Complaints

Abstract: The relationship between habitual sleep and cognition in older adults with sleep complaints is poorly understood, because research has focused on younger adults, used experimental or retrospective quasi-experimental designs, and generally produced equivocal results. Prospective studies using sleep diaries are rare, but may provide important insights into this relationship as they offer greater ecological validity and allow for examination of the impact of night-to-night variability in sleep (an often overlooke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
(55 reference statements)
1
23
0
Order By: Relevance
“…Although sleep did not negatively affect SDMT performance in individuals without a history of chronic pain, our daily findings for this group are consistent with our previous results showing that poor sleep (ie, greater total wake time) is associated with better average processing speed and selective attention performance over 2 weeks of baseline. 10 Specifically, in the current study, we found that greater self-reported WASO led to better next-day performance on SDMT. It is possible that increased WASO at night may lead to a hyperaroused state 11 which then in turn leads to better next-day cognitive performance in those without a history of chronic pain, at least on a cognitive task that measures lower level processing.…”
Section: History Of Chronic Pain (N = 33)supporting
confidence: 49%
See 1 more Smart Citation
“…Although sleep did not negatively affect SDMT performance in individuals without a history of chronic pain, our daily findings for this group are consistent with our previous results showing that poor sleep (ie, greater total wake time) is associated with better average processing speed and selective attention performance over 2 weeks of baseline. 10 Specifically, in the current study, we found that greater self-reported WASO led to better next-day performance on SDMT. It is possible that increased WASO at night may lead to a hyperaroused state 11 which then in turn leads to better next-day cognitive performance in those without a history of chronic pain, at least on a cognitive task that measures lower level processing.…”
Section: History Of Chronic Pain (N = 33)supporting
confidence: 49%
“…7,8 A study examining sleep quality and cognitive performance in older adults with insomnia found that poor sleep quality was associated with worse performance on tests measuring on executive functions (eg, working memory, attentional set shifting, abstract reasoning), but was not associated with episodic memory or processing speed. 9 Interestingly, we also previously reported results showing that longer total wake time was associated with better performance on a sustained attention and processing speed task, 10 suggesting that increases in nighttime wakefulness may translate to a state of hyperarousal that provides a benefit to lower level cognitive processing. 11 However, these findings represented aggregate patterns of average performance across 2 weeks rather than daily patterns of association and did not consider the effects of chronic pain.…”
mentioning
confidence: 72%
“…Several researchers have noted this “functional weakening” possibility (Edinger et al, 2000; Kronholm, 2012; McCrae et al, 2012; Pace-Schott & Spencer, 2011; Schmidt, Peigneux, & Cajochen, 2012; Scullin, 2013; Spiegel et al, 1986), and some supportive evidence was observed in most of the reviewed literatures. Though functional weakening remains relatively unexplored, this view uniquely predicts that increasing the quantity of sleep in older adults is unlikely to restore cognitive abilities because age-related neurobiological changes (e.g., neural atrophy, decreased plasticity, nocturnal hypoxia, neuroendocrine changes, altered neuromodulation) that are presumably necessary to support sleep-specific cognitive processes will still be impaired.…”
Section: Conclusion and Interpretationsmentioning
confidence: 71%
“…Increased nighttime awakenings were associated with poor memory in one small sample study (Mary, Schreiner, & Peigneux,, 2013; see also Sampaio, Sampaio, Yamada, Tsuboyama, & Arai, 2013), but puzzlingly, at least four studies have found the opposite pattern (Foley et al, 1995; Maggi et al, 1998; McCrae, Vatthauer, Dzierzewski, & Marsiske, 2012; Miller et al, 2014). The peculiar finding that greate wake time at night could be related to better cognitive performance in older adults is in notable contrast to the findings in young and middle- aged adults.…”
Section: Self-report Studiesmentioning
confidence: 99%
“…Insomnia coupled with short sleep duration (<6 hours) also appears to have a greater impact on cognitive dysfunction when compared to insomnia with normal sleep duration and healthy sleep patterns (Fernandez-Mendoza et al, 2010). Only one study has examined the impact of sleep variability on cognition, (McCrae et al, 2012) revealing that night-to-night variability in sleep duration and total wake time did not predict performance on a processing speed or an executive functioning task in older adults.…”
Section: Introductionmentioning
confidence: 99%